SYNTACTIC AWARENESS AND WRITING ABILITY OF ENGLISH DEPARTMENT STUDENTS - Maharani, Gita Nathania; Prayogo, Johannes Ananto; Masduqi, Harits (Jurnal Bilingual, 2024)
This study aims to determine the correlation between English learners’ syntactic awareness and writing ability. It was carried out with 30 students from the 2018 cohort of the Department of English at Universitas Negeri Malang. A syntactic awareness and descriptive writing tests were used to obtain data. The data was analyzed using Pearson's correlation coefficient formula, Pearson product-moment formula, and SPSS 21 software by the researchers. According to the findings, with a mean score of 83.2 for the syntactic awareness test and 83.3 for the writing test, both the syntactic awareness and writing test results are satisfactory. The results also show a positive correlation between syntactic awareness and writing ability (the result was 0.702 with a significant level of 0.01, indicating a high-level correlation. Finally, the researchers suggests that lecturers emphasize the importance of syntactic awareness when it comes to improving their students' writing skills. It is also suggested that future researchers conduct further research on syntactic awareness as a strategy to improve the writing ability of English students.